EVALUASI PENYAJIAN LAPORAN KEUANGAN DINAS PEKERJAAN UMUM KOTA BITUNG BERDASARKAN PENERAPAN PERATURAN PEMERINTAH NO. 71 TAHUN 2010 - Rombebunga, Frenly; Saerang, David P. E.; Budiarso, Novi Swandari (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The purpose of this study is to determine whether the presentation of financial reports Municipal Public Works Bitung has been in accordance with Governmental Accounting Standard PP. 71 Year 2010. Type of research conducted is a case study. Data were obtained by interview, observation and documentation. The data taken is the history and development of agencies, agency goals, organizational structure of agencies, geographic conditions and boundaries, vision and mission of the institution, as well as Financial Reports Public Works Department of Bitung City. The analysis technique used is descriptive explorative analysis technique. The steps used in this study is to collect the required data, and then compare the financial report of Bitung City Public Works Department with the financial statements in accordance with the presentation of financial statements based on Governmental Accounting Standard PP. 71 Year 2010. The results showed that the Public Works Department of Bitung City has applied Standa r Accounting Government PP. 71 Year 2010, although not yet optimal, because there are some points that are still incomplete in financial reporting such as Balance Over Change Budget Report (SAL). From twenty-three paragraphs regulating the financial report of Bitung City Public Works Department there are twenty paragas that have been in accordance with Governmental Accounting Standard PP. 71 of 2010. Three paragraphs that have not been applied are included in the Budget Breakdown of More Budget Changes (SAL) report. Keywords: Government Accounting Standards, Department of Public Works, Financial Statements